Vertebral Stenting and Vertebroplasty Guided by an Angiographic 3D Rotational Unit - Escobar-de la Garma Víctor Hugo; Jorge-Barroso Henry Luis; Padilla-Vázquez Felipe; Balderrama-Bañares Jorge Luis (Case Reports in Orthopedics)
Introduction. Use of interventional imaging systems in minimally invasion procedures such as kyphoplasty and vertebroplasty gives the advantage of high-resolution images, various zoom levels, different working angles, and intraprocedure image processing such as three-dimensional reconstructions to minimize complication rate. Due to the recent technological improvement of rotational angiographic units (RAU) with flat-panel detectors, the useful interventional features of CT have been combined with high-quality fluoroscopy into one single machine. Intraprocedural 3D images offer an alternative way to guide needle insertion and the safe injection of cement to avoid leakages. Case Report. We present the case of a 72-year-old female patient with insidious lumbar pain. Computed tomography revealed a wedge-shaped osteoporotic compression fracture of T10 vertebrae, which was treated successfully with the installation of vertebral stenting system and vertebroplasty with methacrylate guided with a rotational interventional imaging system. Conclusion. Rotational angiographic technology may provide a suitable place for the realization of high-quality minimally invasive spinal procedures, such as kyphoplasty, vertebroplasty, and vertebral stenting. New software programs available nowadays offer the option to make three-dimensional reconstructions with no need of CT scans with the same degree of specificity.